FOSL2 Is Involved in the Regulation of Glycogen Content in Chicken Breast Muscle Tissue - Liu, Xiaojing; Liu, Lu; Wang, Jie; Cui, Huanxian; Zhao, Guiping; Wen, Jie (Frontiers in Physiology, 2021)
In chicken, the glycogen content of muscle affects the homeostasis of the body, growth performance and meat quality after slaughter. We previously identified FOSL2(FOS like 2, AP-1 transcription factor subunit, also known as Fos-related antigen 2 (FRA2)) as a candidate gene significantly related to muscle glycogen (MG) content. However, the molecular mechanism by which FOSL2 regulates MG content has not been elucidated. Differential expression analysis (DEG) and Weighted Gene Co-Expression Network Analysis (WGCNA) were performed on breast muscle tissues from the higher MG content group (HMG) and the lower MG content group (LMG) Jingxing yellow chickens. The influence of breed and sex was verified using male and female Beijing You chickens. Additionally, we investigated the effects of lentiviral-mediated overexpression of FOSL2 on the glycogen content of chicken fibroblast DF1 cells in vitro. DEG analysis identified a total of 1,171 significantly DEGs, including PRKAG, CEBPB, FOSL2, FOXO1, AMPK, and PIK3C, which are genes functionally related to MG. Besides showing that FOSL2 expression is negatively correlated with MG content, WGCNA also revealed that CEBPB, MAP3K14, SLC2A14, PPP2CA, SLC38A2, and PPP2R5E and other classic glycogen metabolism-related genes are also related to MG content and co-expressed with FOSL2.In addition, DEG analysis and WGCNA also revealed that FOSL2 is co-expressed with multiple classic genes related to glucose metabolism. Overexpression of FOSL2 in DF1 cells decreased their glycogen content. Collectively, our results suggest that FOSL2 has a key role in regulating the MG content in chicken muscle tissue. This finding is useful for the study of the regulatory mechanism of chicken MG metabolism, to develop a theoretical basis for the genetic improvement of muscle metabolism traits of chicken muscle tissue and a comprehensive nutritional control strategy.